Pengaruh Persepsi Mahasiswa tentang Berita-berita Kriminal di Televisi terhadap Kecemasan yang Ditimbulkannya - Jamiatul llmi, Saeri Tri Kusumo, dan Bimono (Jurnal Psikologi, 2010)
Objective of this study is to understand the relationship between students’ perception on criminal news in television and their worry because of watching criminal news in television. It was about 60 university students from a boarding house participated in this study. The independent variable is student's perception on criminal news in television, whilst the dependent variable is student's worry because of watching criminal news in television. The ru of the Perception Scale was ranged .36-75, whilst the r„ for the Worry Scale was about .336-764. The hypothesis analysis using the product moment correlation revealed that there was a significant relationship between students perception on criminal news in television and students worry because of watching criminal news in television (r„ ■ .430, p <.01). Contribution of the perception variable on influencing worry variable was only 18.5%. Several recommendations for future research and explanation on other influencing variables outside of these research variables were discussed.